Reproductive effort alters immune parameters measured post‐partum in European rabbits under semi‐natural conditions. (20th April 2016) - Rödel, Heiko G.; Zapka, Manuela; Stefanski, Volker; von Holst, Dietrich
Summary: Reproduction is energetically costly, and females frequently trade off their reproductive effort with allocation to other physiological processes. One of these processes is the maintenance of a functional immune defence. However, such interactions between immunity and reproduction have rarely been explored in mammals under natural conditions. In our study on females of an individually marked European rabbit Oryctolagus cuniculus colony, we measured different components of the maternal immune system from peripheral blood and serum 1 day after parturition, and we associated variation in these measures with differences in mothers' reproductive effort. We used total litter mass as a measure of the mother's current reproductive effort. In addition, we recorded whether or not mothers gave birth and nursed another litter shortly before and considered this a measure of prior reproductive effort. Mothers with higher current or prior reproductive effort showed generally lower concentrations of white blood cells, in particular neutrophils and lymphocytes, but a higher activity of the complement system and higher IgG serum concentrations than females with lower reproductive effort. We obtained similar results when comparing individual changes in immune parameters measured post‐partum across repeated reproductive events. Cell concentrations of neutrophils and lymphocytes increased when individual females decreased their reproductive effort. In contrast, IgG serum concentrations and the activity of the complement system increased when mothers increased their reproductive effort. In conclusion, the results underline differential responses of different branches of the maternal post‐partum immune system to variation in reproductive effort. On the one hand, our study indicates that females might compromise at least some cellular immune parameters for reproduction. On the other hand, the positive association between IgG concentrations and reproductive effort could be adaptive as a higher litter mass and higher number of pups requires an intensified transfer of this immune parameter via placenta or colostrum and milk. This positive association might constitute an additional, immunological component of the energetic costs of reproduction. A lay summary is available for this article. Abstract : Lay Summary